GREECE, PORTUGAL AND SPAIN - A TEST CASE FOR EUROPE IN 2011 - CRISTINA RALUCA POPESCU; VERONICA ADRIANA POPESCU; GHEORGHE N. POPESCU (Challenges of the Knowledge Society)
Recent statistics clearly show that Greece, Portugal, Spain and other euro zone members have massive public deficits and that is why this entire means that euro's future is extremely delicate. Until now, politicians have not come up with a concrete plan to solve the situation. In this matter, politicians in France, Germany and elsewhere have signaled that they'll provide some kind of back-up support, but only when Greece has really taken tough measures – possibly more than they have done already – to get the deficit down. Although that may be unsettling to some investors in the very short term, it's clearly good news for the euro in the longer term. In our paper, the intention is to present the reasons why Greece, Portugal, Spain and other euro zone members have massive public deficits and what should other countries do in order to help them in the nearby future. For us, a great concern is also the reaction of the European Central Bank and what could this institution do in the benefit of European countries in general.